Evaluating evidence‐based practice in light of the boundedness and proximity of outcomes: Capturing the scope of change. Issue 8 (4th May 2021) - Sandbank, Micheal; Chow, Jason; Bottema‐Beutel, Kristen; Woynaroski, Tiffany
Abstract: Evidence‐based practice (EBP) reviews abound in early childhood autism intervention research. These reviews seek to describe and evaluate the evidence supporting the use of specific educational and clinical practices, but give little attention to evaluating intervention outcomes in terms of the extent to which they reflect change that extends beyond the exact targets and contexts of intervention. We urge consideration of these outcome characteristics, which we refer to as "proximity" and "boundedness, " as key criteria in evaluating and describing the scope of change effected by EBPs, and provide an overview and illustration of these concepts as they relate to early childhood autism intervention research. We hope this guidance will assist future researchers in selecting and evaluating intervention outcomes, as well as in making important summative determinations of the evidence base for this population. Lay Summary: Recent reviews have come to somewhat different conclusions regarding the evidence base for interventions geared toward autistic children, perhaps because such reviews vary in the degree to which they consider the types of outcome measures used in past studies testing the effects of treatments. Here, we provide guidance regarding characteristics of outcome measures that research suggests are particularly important to consider when evaluating the extent to which an intervention constitutes "evidence‐based practice."